BIBLIOMETRIC STUDY OF POROUS ASPHALT IN INDONESIA USING VOSVIEWER SOFTWARE - Zenita Sabitri; Zahra Ghinaya; Jasmine Al Dhahrani; Sri Rahayu (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
This research collects and processes with the aim of examining the development of research on porous asphalt in Indonesia using a bibliometric approach with utilize VOSviewer application. The data is acquired from Google Scholar using publish and perish as the reference manager application. In the data search process, researchers used the keywords ‘porous’, 'porous asphalt' and 'Indonesia' as a reference so that search results were concentrated and facilitated mapping. From the search results, 224 articles have been found that are relevant to the keywords used. The research time span used as study material is an article contained in Google Scholar for the last 5 years (2018-2022). The results of this research of porous asphalt can be divided into 3 parts, namely asphalt, porous asphalt and Indonesia. The term “asphalt” is associated with 42 links with 233 total link strength. The term “Porous Asphalt” is associated with 25 links with 62 total link strength. For 'Indonesia' is associated with 44 links and 254 total link strength. based on the results of the analysis show an increase in the number of studies on porous asphalt in Indonesia every year but the increase is not so high and so that it can be said that it is still rare